THE RELATION BETWEEN STUDENTS’ ANXIETY AND READING COMPREHENSION - Dewi Wahyuning Astuti; Nadia Fairuz Haris (PROJECT (Professional Journal of English Education), 2018)
This study aims to analyze the relation of Students’ anxiety and reading comprehension  among senior high school students in Klari Karawang, West Java Province, Indonesia. Participants of this study were thirty students of twelve grade at  SMAN 1 Klari Karawang The study was conducted with a quantitative approach and performed in Klari, Karawang. Based on the findings, the result show there is no significant correlation in Students’ anxiety because in the data show the significant is 0,051 more than 0,05 (> 0,05). The result also show there is no significant correlation in Reading comprehension because in the data show the significant is 0,051 more than 0,05 (> 0,05). Based on the data obtained from thirty participants showed that treat anxiety is 10% , state anxiety is 17%  and situation specific anxiety is 73%.  Measurement of reading  anxiety was done by using Foreign Language Reading Anxiety Scale (FLRAS). Moreover, the researcher give a suggestion for teacher to make a preventive activity, for example to avoid students’ anxiety in reading comprehension, the teacher can provide comfort environment in learning activity, it will help to decrease students’ level of anxiety and it is necessary to motivate student to increase their desire to read more English text and understand the context.